Biochemical and haematological parameters in dogs with Cushing's syndrome - Karić, Ernes (Array, 2021)
The exposure of the body to stress, regardless of whether it comes from physical, chemical or emotional stimuli from the environment, causes an inadequate adaptation of the organisms which can contribute to the development of various diseases. Abnormally high blood concentrations of cortisol, known as stress hormone, lead to the development of a hormonal disorder called hyperadrenocorticism or Cushing"s syndrome. In the majority of cases, Cushing"s syndrome is diagnosed when symptoms are apparent, and screening endocrinological test confirms the existence either of increased cortisol production or decreased sensitivity of the hypothalamic-pituitary-adrenal axis to negative glucocorticoid feedback. In our research, we examined a total of 23 male and 7 female dogs that were suspected to have Cushing"s syndrome, based on history and clinical signs. A total of 15 male and 5 female dogs were positive for Cushing"s syndrome (HAC group), whereas the  remaining dogs were used to form non-HAC group. Using the apparatus IDEXX "Vet Test 8008", the following biochemical parameters were determined: glucose, urea, creatinine, phosphorus, calcium, total protein, albumin, globulin, alanine aminotransferase, alkaline phosphatase, bilirubin, cholesterol, and amylase. Regarding haematological parameters, the following parameters were investigated: erythrocytes, leukocytes, platelets, erythrocyte indices (MCV, MCH, MCHC, RDW), white blood cell count, haemoglobin and haematocrit, using "Laser cite vet lab Station" (IDEXX). No significant differences in haematological and biochemical blood parameters were noticed between the HAC and the non-HAC group of dogs. However, dogs suffering from Cushing"s syndrome had a higher value in the number of erythrocytes compared to the control group.